The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1002/cmdc.201500385
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Selective Inhibitors of Trypanosoma cruzi Triosephosphate Isomerase with Concomitant Inhibition of Cruzipain: Inhibition of Parasite Growth through Multitarget Activity

Abstract: Triosephosphate isomerase (TIM) is an essential Trypanosoma cruzi enzyme and one of the few validated drug targets for Chagas disease. The known inhibitors of this enzyme behave poorly or have low activity in the parasite. In this work, we used symmetrical diarylideneketones derived from structures with trypanosomicidal activity. We obtained an enzymatic inhibitor with an IC50 value of 86 nm without inhibition effects on the mammalian enzyme. These molecules also affected cruzipain, another essential proteolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 43 publications
1
66
0
1
Order By: Relevance
“…Screening FhTIM. We hypothesized that a TIM dimer interface inactivator would be a successful strategy to identify molecules with selective antiparasitic activity [18][19][20] . Therefore, we selected 340 compounds from our in-house chemical collection and screened them against the isolated recombinant FhTIM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening FhTIM. We hypothesized that a TIM dimer interface inactivator would be a successful strategy to identify molecules with selective antiparasitic activity [18][19][20] . Therefore, we selected 340 compounds from our in-house chemical collection and screened them against the isolated recombinant FhTIM.…”
Section: Resultsmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Cell culture. J774.1 murine macrophage cells (ATCC, USA) were grown in DMEM culture milieu containing 4 mM glutamine and supplemented with 10% FCS 20 . The cells were seeded in a 96-well plate (5×10 4 cells in 200 µL culture medium) and incubated at 37 °C in a 5% CO 2 atmosphere for 48 h, to allow cell adhesion prior to drug testing.…”
Section: Inhibition Of Triosephosphate Isomerase Expression and Purimentioning
confidence: 99%
“…In this study, we can relate the importance of loop 6 and loop 7 in the development of drugs against TcTIM and GlTIM, and we propose than, our important amino acids are in the loop 3 region, which alter the region of the interface and C4 has a greater effect with the loop 7, resulting in the alteration of the conformational structure of the active site or that some conformation interacts with Lys14 or His97 that decreases glycolytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…One of the enzymes validated in the study of promising targets for the treatment of Chagas disease is the triosephosphate isomerase (TIM), of which its existing inhibitors have low interactions. For this reason, Aguilera et al (2016) reported the study of derivatives diarylideneketones ( Figure 6) in antitrypanosomal activity, with in vitro and IC 50 in the range of 86 nM, without having negative effects on the mammalian enzyme. In addition to this activity, inhibition of 31% for the cruzain enzyme was also reported.…”
Section: Chagas Disease: Trypanossoma Cruzimentioning
confidence: 99%